203 Outcomes of patients with discordant CSF bilirubin and oxyhaemoglobin xanthochromia Results a retrospective audit. Issue 6 (27th May 2022) - Day, Jacob; Gower, Hannah; Gormley, Joe
Abstract : Background: Investigation of headaches for possible subarachnoid haemorrhage frequently involves examination of cerebrospinal fluid (CSF) for xanthochromia. If both CSF bilirubin and oxyhaemoglobin are raised it is suggestive of subarachnoid haemorrhage and if both are negative this is reassuring. However, when one of the CSF bilirubin or oxyhaemoglobin is raised in isolation it is unclear what the risk of suba- rachnoid haemorrhage is. Method: We performed a retrospective audit of all CSF analyses for xanthochromia in a single centre over a 2 year period in 2016–2018. Of the 403 results, 10 had raised CSF bilirubin or oxyhaemoglobin in isolation. 6 had raised oxyhaemoglobin that could impair the ability to detect CSF bilirubin; 4 had raised CSF oxyhaemoglobin which could be due to blood or other causes. Results: Overall, there was only 1 confirmed subarachnoid haemorrhage and this was traumatic. Of the 9 other cases, 5 were a primary headache, 1 viral meningitis, 1 viral encephalitis, 1 bacterial meningitis and 1 autoimmune encephalitis. In the 18 months since the end of the audit period no patient has re- presented with subarachnoid haemorrhage. Conclusion: We found no cases of aneurysmal subarachnoid haemorrhage in patients with isolated raised CSF bilirubin or oxyhaemoglobin. jacobday@doctors.org.uk